2020
DOI: 10.1177/1555343419892184
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Workload and Workload Transitions on Attention Allocation in a Dual-Task Environment: Evidence From Eye Tracking Metrics

Abstract: High mental workload, in addition to changes in workload, can negatively affect operators, but it is not clear how sudden versus gradual workload transitions influence performance and visual attention allocation. This knowledge is important as sudden shifts in workload are common in multitasking domains. The objective of this study was to investigate, using performance and eye tracking metrics, how constant versus variable levels of workload affect operators in the context of a dual-task paradigm. An unmanned … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 60 publications
0
4
0
1
Order By: Relevance
“…Moacdieh et. al [60] found that the preference-based workload allocation method has benefits on workload allocation, while Wigboldus et. al [61] proposed that capability-based workload has greater productivity and effectiveness.…”
Section: Discussionmentioning
confidence: 99%
“…Moacdieh et. al [60] found that the preference-based workload allocation method has benefits on workload allocation, while Wigboldus et. al [61] proposed that capability-based workload has greater productivity and effectiveness.…”
Section: Discussionmentioning
confidence: 99%
“…B. Moacdieh et al. 2020 ). Die unterschiedlichen Rahmenbedingungen der einzelnen Studien erschweren den direkten Vergleich der angewandten Messgeräte und -verfahren untereinander.…”
Section: Bausteine Der Experimentalaufgabeunclassified
“…Whether the studies use touch screen, fNIRS, eye-tracking data to measure performance and subjective cognitive load, a further work is needed to better understand the relationship between cognitive load and predicting task performance. A recent study has investigated the difference between sudden and gradual workload transitions in terms of performance during a task but not at the initial of the task [41]. Being able to determine the cognitive load of a task at the initial of the task can be used to improve those interfaces that are sensitive to time.…”
Section: Related Workmentioning
confidence: 99%